Editorial: The Social Dimension of Teacher Knowledge Building - Quintero Polo, Álvaro Hernán; Bonilla Medina, Sandra Ximena (Colombian Applied Linguistics Journal, 2020)
This issue of the Colombian Applied Linguistics Journal – CALJ – contains articles that relate to one of the main goals of research, namely, to transform already existing knowledge or to produce new knowledge. Knowledge as a multidimensional notion is one that is worthy of editorial efforts. Fullan (2001) makes a distinction between information and knowledge by maintaining that information is machines and knowledge is people. The latter idea implies that individual and collective social actors play roles in transforming tacit knowledge into shared knowledge. The article authors in this CALJ issue put forward their knowledge for others to understand, debate, acknowledge or refuse it. These are the collective and interactional traits of knowledge which is the social dimension of it; information becomes knowledge when it obtains social life (Piñeros & Quintero, 2006).